EFFECT OF THE MUSCLE BIOCHEMICAL CHARACTERISTICS ON THE TENDERNESS OF AGED MEAT IN YOUNG GOATLING (CAPRA NUBIANA) ANIMALS - Cuenca-Mendoza F.; C. Gonzalez; M. A. Ruiz-Cabrera; D. L. González-Navarro; R. González-García; L. González-Juárez; M. Gil; A. Grajales-Lagunes (Journal of Animal and Plant Sciences, 2015)
The effect of muscle biochemical characteristics on the tenderness of goatling meat was examined in Semimembranosus (SM), Semitendinosus (ST) and Longissimus (L) muscles. Twelve goatling of Nubia breed were slaughtered at 55 days of age, the muscles were obtained at 1 hour postmortemand aged for 8 days at 4ºC.pH decline rate, metabolism, contraction rate, cathepsins B and B+L activities and tenderness (myofibrillar toughness) were evaluated at different ageing times. This study showed that in goatling muscles, the pH decline rate and metabolism type directly influencedon the activity of cathepsins B+L andtheir activity decline rate.Cathepsin B+L activity presented a quadratic correlation (R2=0.88) with myofibrillar toughness and it was associated with the final meat tenderness.The term “goatling” refers only to young animals and it is suggests that an ageing period is necessary to improve theirtenderness.
Keywords: goatling; metabolism; myofibrillar toughness; tenderness; pH; cathepsins